Meet Me in My World: a creative prosimetric reconstruction of Aislinge Óenguso - Roxanne Bodsworth (Ceræ)
Aislinge Óenguso (The Dream of Óengus) is an eighth-century Irish tale extant only in the sixteenthcentury MS Egerton 1782. A woman visits Óengus in his dreams and he subsequently develops a love-sickness. A search is instigated by his family for the woman, and they learn that she is Caer, the daughter of Ethal Anbúail in the region of Connacht. However, Caer exists sometimes as a swan, sometimes a woman, and this animistic duality places her outside paternal or political control; she cannot be given to Óengus. Instead, Óengus undergoes a metamorphosis into a swan so they can be united. While this is the nucleus of the tale, the greater part of the discourse is given over to Óengus, politics, and battles, such that the female experience is rendered subsidiary to the male journey. In this prosimetric reconstruction called Meet Me in My World, the tale of Aislinge Óenguso is retold in desegmented syllabic quatrains that echo the strict formulations of medieval Irish poetry, while the lacuna of the female experience is excavated in free verse. This serves to foreground the feminine and thus alters the discourse from one of phallocentric satisfaction to female autonomy while retaining the framework of the eighth-century traditional tale.